2013
DOI: 10.3390/md11114558
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Neutral Lipid and Polyunsaturated Fatty Acid Biosynthesis by Overexpressing a Type 2 Diacylglycerol Acyltransferase in Marine Diatom Phaeodactylum tricornutum

Abstract: Microalgae have been emerging as an important source for the production of bioactive compounds. Marine diatoms can store high amounts of lipid and grow quite quickly. However, the genetic and biochemical characteristics of fatty acid biosynthesis in diatoms remain unclear. Glycerophospholipids are integral as structural and functional components of cellular membranes, as well as precursors of various lipid mediators. In addition, diacylglycerol acyltransferase (DGAT) is a key enzyme that catalyzes the last ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(131 citation statements)
references
References 27 publications
4
124
1
Order By: Relevance
“…Various genetic modification approaches have been applied on diatoms (Armbrust et al, 2004;Hu et al, 2008;Niu et al, 2013). P. tricornutum over-expressing heterologous thioesterase increased 72% of total fatty acid content (Gong et al, 2011).…”
Section: Genetic Modificationsmentioning
confidence: 99%
“…Various genetic modification approaches have been applied on diatoms (Armbrust et al, 2004;Hu et al, 2008;Niu et al, 2013). P. tricornutum over-expressing heterologous thioesterase increased 72% of total fatty acid content (Gong et al, 2011).…”
Section: Genetic Modificationsmentioning
confidence: 99%
“…Genetic manipulations of lipid production in the model diatom, Phaeodactylum tricornutum, are ambiguous. Although there is one report showing that an overexpression of a type II diacylglycerol acyltransferase (DGAT; ProtID 49462) involved in TAG biosynthesis increases the accumulation of natural lipids in P. tricornutum (15), there are several reports indicating that manipulating FA biosynthesis does not significantly affect rates of lipid production (13,14,16).…”
mentioning
confidence: 99%
“…Increasing the lipid content of rapidly growing microalgae is a desirable approach to producing biodiesel by cell culture. To date, significant advances in microalgal genomics have been achieved [6,27], and two reports of enhanced lipid content of diatoms due to genetic engineering have been published [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Trentacoste et al successfully increased microalgal lipid accumulation without compromising the growth in Thalassiosira pseudonana by a knockdown of a multifunctional lipase/phospholipase/ acyltransferase [16]. Niu et al found that the overexpression of an acyl-Coenzyme A:diacylglycerol acyltransferase gene in Phaeodactylum tricornutum can increase lipid biosynthesis [17]. In addition to genes that are directly related to lipid metabolism, many valuable transcription factors (TFs) that are involved in the regulation of lipid synthesis in higher plants have been identified in recent years [18].…”
Section: Introductionmentioning
confidence: 99%